The COVID-19 Pandemic and Its Implications for the Performance of the Maqashid Syariah Index of Sharia Banks - Regina Meidista Damayanti; Agus Eko Sujianto; Nurul Hidayah (Jurnal Manajemen Bisnis, 2023)
The purpose of this study was to test the comparative financial performance of Islamic Commercial Banks in Indonesia and Malaysia before and during the Covid-19 pandemic when viewed from all indicators of the maqashid syariah index. The sample in this study used a purposive sampling method obtained by 7 Indonesian Islamic Banks and 8 Malaysian Islamic Banks. The data analysis technique uses the performance measurement of Maqashid Syariah. The results of the study show that when viewed from all indicators of the maqashid syariah index, there are differences in the financial performance of Islamic Commercial Banks in Indonesia and Malaysia before and during the Covid-19 pandemic.